Взрыв фрагмента кометного ядра в атмосфере Земли - Кручиненко, В.Г.; Чурюмов, К.И.; Чурюмова, Т.К. (Кинематика и физика небесных тел, 2011)
Проведен анализ данных о тепловых взрывах крупных метеороидов в атмосфере Земли. Исправлена кумулятивная функция притока космических тел с учетом высоты взрыва, определяемой, согласно нашей концепции, максимальным торможением. Это привело к согласию интегральной функции притока, приведенной в работе [Brown P., Spalding R. E., ReVelle D. O., et al. The flux of small near-Earth objects colliding with the Earth // Nature.—2002.—420.—P. 314—316], и ранее полученной нами. Обнаружено, что по крайней мере одно явление из приведенных в работе — результат взрыва кометоида. Показано, что Тунгусский феномен невозможно объяснить в рамках модели монолитного тела. Виконано аналіз даних теплових вибухів великих метеороїдів в атмосфері Землі. Виправлена кумулятивна функція допливу космічних тіл з врахуванням висоти вибуху, яка, згідно з нашою концепцією, визначається максимальним гальмуванням. Це привело до узгодження інтегральної функції, наведеної в роботі [Brown P., Spalding R. E., ReVelle D. O., et al. The flux of small near-Earth objects colliding with the Earth // Nature.— 2002.—420.—P. 314—316], і раніше отриманої нами. Виявлено, що принаймні одне явище з наведених в роботі є результатом вибуху кометоїда. Показано, що Тунгуський феномен неможливо пояснити в рамках моделі монолітного тіла. We analysed some data on thermal explosions of arge meteoroids in the Earth’s atmosphere. The cumulative function of influx of space bodies is corrected with taking into account an explosion height. According to our onception, the explosion height is determined by maximal braking. As the result of this, the integral function of influx from the paper of Brown P. et al [Brown P., Spalding R. E., ReVelle D. O., et al. The flux of small near-Earth objects colliding with the Earth // Nature.—2002.— 420.—P. 314—316] and one derived by the authors earlier are in good agreement. It is found that at least one phenomenon from the paper is a result of an explosion of a comet nucleus fragment. It is shown that the Tungusska phenomenon can not be explained within the framework of a monolithic body model.